Capital market reform in Asia : towards developed and integrated markets in times of change - Kawai, Masahiro, 1947-; Sheng, Andrew (SAGE, 2012)
Capital Market Reform in Asia is a compilation of selected papers that captures the essence of the issues and challenges that contributed to capital market reform in the Asian region. The central theme of this volume is to chart the progress of capital market development in Asia after the 1997-1998 Asian financial crisis, to understand the complex process of capital market deepening in emerging market economies, and to acknowledge that in the aftermath of the global financial crisis of 2007-2009, robust Asian capital markets are crucial for mobilizing domestic savings for investments in Asia,